PENGARUH PEMBAYARAN PAJAK SECARA ONLINE TERHADAP KEPUASAN WAJIB PAJAK DENGAN VARIABEL MEDIASI DIGITAL LITERACY DI KPP PRATAMA CIMAHI - Angela Sabatini Lappra; Lenita Waty; Rolyana Ferinia Pintauli (JURNAL LENTERA BISNIS, 2025)
Indonesia as a developing country, is increasingly utilizing digitalization to facilitate various transactions, including tax payments. Taxpayer satisfaction is an indicator used to measure the effectiveness of tax services, which can encourage compliance. This study aims to analyze the impact of online tax payments on digital literacy and taxpayer satisfaction, as well as the mediating role of digital literacy. The research was conducted on corporate taxpayers registered at KPP Pratama Cimahi using purposive sampling, involving 180 respondents. Data collection was done through questionnaires measured using a Likert scale. The data analysis technique used was Structural Equation Modeling Partial Least Squares (SEM-PLS) method.  The results showed that online tax payment has a significant impact on digital literacy (H1 accepted), but does not directly have a significant impact on taxpayer satisfaction (H2 rejected). Digital literacy has a significant impact on taxpayer satisfaction (H3 accepted) and mediates the relationship between online tax payment and taxpayer satisfaction (H4 accepted). The study concludes that improving digital literacy can strengthen the positive impact of using the online tax payment system on taxpayer satisfaction. The government needs to enhance socialization and digital infrastructure, as well as provide ongoing training to support the utilization of technology in tax payments.